Interreligious Tolerance in Higher Education: Students’ Perceptions at the Faculty of Agriculture, Universitas Brawijaya - Felia, Luna Ananta; Nurrochman, Tria; Khoiriyyah, Siti (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
Tolerance between religious communities is reflected in actions or deeds that show mutual respect, respect, help, and love. This study aims to determine the views of Brawijaya University students, especially the Faculty of Agriculture, on inter-religious tolerance in the campus environment. This research data is in the form of words and sentences obtained from the perceptions of students of the Faculty of Agriculture, Universitas Brawijaya. Data collection techniques were carried out through distributing and filling out questionnaire forms. The research method used is a questionnaire survey method on 30 students. The results obtained show that many students of the Faculty of Agriculture are concerned about the importance of tolerance in Brawijaya University, in order to create harmony between students with each other. They think that tolerance is very important to be applied to the campus environment, because there are various students from various regions who have differences with each other.